Breeding phenology and landscape use in all amphibian species from the Republic of Korea based on open-source data - Groffen, Jordy; Andersen, Desiree; Borzée, Amaël (Frontiers in Environmental Science, 2022)
Biodiversity is declining worldwide with habitat loss and climate change being among the main threats. While it is easy to quantify habitat loss, the impacts of climate change are less obvious. It is therefore important to understand species habitat use and breeding phenology before a significant shift results in the loss of knowledge. Here, we determined the habitat use and breeding phenology for all Korean amphibian species based on citizen science (8,763 observations), collected between 1997–2020. We found the breeding seasons as we defined them to be generally shorter than described in the literature despite large variations between species. Species were further dichotomised into early and late breeders with breeding periods peaking in mid-March and mid-June respectively. We found early breeding species to have a shortened hibernating period with only six days being consistently devoid of observations over the 23 years of the period studied for the species with the shortest inactive season. Habitat use was significantly different between all species, with pair-wise comparisons highlighting greater differences among rather than within genera, highlighting the threats to species across all genera. In addition, our results set a baseline for future analyses about climate change and habitat use.